ANALYSIS ON DYNAMIC CHARACTERISTICS OF CYLINDRICAL ROLLER BEARING UNDER THE CONDITION OF ROTATIONAL SPEED FLUCTUATIONS - TU WenBing; HE HaiBin; LIU LePing; LUO Ya; WANG ChaoBing (Jixie qiangdu)
The research on the dynamic characteristics of roller bearings is mainly concentrated on steady condition, but the rotational speed fluctuations exist in many rotating machines, and it has important influence on the dynamic performance of rolling bearing. Taking cylindrical roller bearing NU306 as investigation object, a nonlinear dynamic finite element model for plastic material flexible contact of a cylindrical roller bearing was established. Based on explicit dynamic LS-DYNA, the dynamic simulations for nonlinear operation process under three different rotational speed fluctuations（rectangular fluctuations, sinusoidal fluctuations and random fluctuations） were made, and the angular speed curve and slipping rate curve of cage and the contact force curve of between roller and inner ring and cage were obtained. The finite element solutions of a cylindrical roller bearing under steady condition were compared with its analytical solutions, and the validity of the established finite element model was verified. The results show that the greater angular acceleration of rotational speed on the inner ring, the greater fluctuations of angular speed curve and slipping rate curve of cage, and negative slipping rate may occur when the fluctuation is serious. Rotational speed fluctuations influence the stability of cage mainly by changing the contact force between rollers in load zone and cage, and rotational speed fluctuations may lead to load zone range larger and make the peak load force of single roller reduce.